Removal of Chromium (III) from Tannery Wastewater by Bioaccumulation Method Using Vallisneria sp. River-weed (Dhaka University Journal of Science, 2015)
The presence of chromium (III) in the wastewater is one of the major concerns for the tannery industry in Bangladesh. In this study the removal of chromium (III) from tannery effluent has been carried out by bioaccumulation method using abundantly available Vallisneria sp. river-weed in river all over Bangladesh. Various factors influencing the uptake of chromium, viz., quantity of river-weed, concentration of chromium (III), pH of the solution and duration of treatment have been optimized. Chemical modifications of the river-weed through pretreatment with H2SO4, CaCl2 and MgCl2 showed improved removal efficiency of chromium (III). Langmuir isotherm has been fitted for 0.5 g of river-weed. The dynamic method of treatment of protonated river-weed with a chromium (III) solution at a pH of 3.2 for duration of 4 days gave the maximum uptake of about 81%. A similar uptake has been established for commercial chrome tanning wastewater. In addition, the potential reuse of chromium-containing river-weed for the preparation of basic chromium sulfate (tanning agent) has been demonstrated.Dhaka Univ. J. Sci. 63(2):91-96, 2015 (July)